SAT0618 Age and Pre-Treatment with Glucocorticoids Influence the B-Mode and Power Doppler Ultrasound (PDUS) Synovitis Scores at the Onset of Inflammatory arthritis. (9th June 2015) - Albrecht, K.; Callhoff, J.; Zink, A.; Backhaus, M.
Abstract : Background: Musculoskeletal ultrasound (US) is used increasingly for the detection of active synovitis and as a prognostic marker for the development of erosions in inflammatory arthritis. Objectives: To evaluate patient-related characteristics of ultrasound outcomes in inflammatory arthritis. Methods: Patients with early inflammatory arthritis were investigated with B-mode (n=434) and power Doppler ultrasound (PDUS, n=280) in an early arthritis cohort. A structured protocol of validated US items was used on the basis of the US7 score [1], including the B-mode and PDUS examination of the clinically most affected hand and foot (wrist, ECU, MCP2, 3 and MTP2, 5). Results were graded from 0-3. A sumscore was obtained from all synovitis gradings in B-Mode (0-21) and PDUS (0-21). An association with a previous use of glucocorticoids was tested by ANCOVA, corrected for age. Patient-related correlates with a B-mode sumscore ≥2 and a PDUS sumscore ≥1 were evaluated by logistic regression analyses. Results: The patients presented with the following mean values: age: 56 years, symptom duration: 13 weeks, DAS28: 5.1, ESR: 31mm/h, SJC: 7, TJC: 11, B-mode sumscore: 4.6±3.7, PDUS sumscore: 2.2±2.5. The mean synovitis and PDUS scores were significantly lower in patients who were pre-treated with glucocorticoids for more than one week (B-mode -1.3, PDUS -0.9, p<0.05) as compared to patients where GCs were to be started. In the univariate analysis, age, DAS28 and osteoarthrosis were associated with B-mode scores >2, age, DAS28, use of high-dose GCs and hypertension with PDUS scores >1. Patients with previous GC use had a decreased probability to present with PDUS signals (OR 0.7). In the multivariate analysis, only age remained associated with B-mode scores (OR 2.0), age and DAS28 (OR 1.03 and 1.9) remained significantly associated with PDUS scores. Conclusions: PDUS and B-mode scores were already decreased in patients who had received glucocorticoids for more than one week. This has to be considered when using them for the assessment of disease activity and as a prognostic marker in early arthritis. References: Backhaus M, Ohrndorf S, Kellner H, et al. Evaluation of a novel 7-joint ultrasound score in daily rheumatologic practice: a pilot project. Arthritis Rheum. 2009 Sep 15;61(9):1194-201. Acknowledgements: The observational cohort was funded by an unconditional grant from Pfizer. Disclosure of Interest: None declared